2005
DOI: 10.1038/ni1228
|View full text |Cite
|
Sign up to set email alerts
|

Loss of adenomatous polyposis coli gene function disrupts thymic development

Abstract: Loss of the adenomatous polyposis coli (APC) protein is a common initiating event in colon cancer. Here we show that thymocyte-specific loss of APC deregulated β-catenin signaling and suppressed Notch-dependent transcription. These events promoted the proliferation of cells of the double-negative 3 and 4 stages and reduced rearrangements between the variable, diversity and joining regions of the gene encoding T cell receptor (TCR) β, encouraging developmental progression of aberrant thymocytes lacking pre-TCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 45 publications
12
105
3
Order By: Relevance
“…For example, recent studies using mice show that loss of Apc impairs T cell differentiation during thymus development. These defects were not fully recapitulated by introduction of stabilized ␤-catenin (35). In addition, Dang et al (36) demonstrated that APC and cdx2 regulate Kruppel-like factor 4, which suppresses proliferation in a ␤-cateninindependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent studies using mice show that loss of Apc impairs T cell differentiation during thymus development. These defects were not fully recapitulated by introduction of stabilized ␤-catenin (35). In addition, Dang et al (36) demonstrated that APC and cdx2 regulate Kruppel-like factor 4, which suppresses proliferation in a ␤-cateninindependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in immunity is substantiated by the existence of documented immune phenotypes in mouse models with mutations in either Apc or Exo1. Apc 1638N mice undergo lymphocyte depletion (Coletta et al, 2004;Gounari et al, 2005), and have defects in cellular immunity. Bardwell et al (2004) have demonstrated that Exo1/dex six mice have deficiency in somatic hypermutation and class switching in B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…During fetal thymocyte development, TCR␤ expression is not necessary for transition from DN3 to DN4 and the majority of the DN4 population do not express icTCR␤ until E17.5. 27 We therefore measured TCR␤ gene rearrangement using a Q-PCR assay, 28 using 5Ј primers to V␤8.2 and V␤5.1 and a 3Ј primer to J␤2.7 ( Figure 2C). We did not detect a statistically significant reduction in either V␤8.2 to J␤2.7 or V␤5.1 to J␤2.7 rearrangement in the Gli2 Ϫ/Ϫ DN cells, relative to WT, suggesting that the reduction in icTCR␤ staining in the DN4 population was most likely the consequence of delayed progression of thymocyte development.…”
Section: Inefficient Differentiation From Dn1 To Dn2 In Gli2 ؊/؊ Thymusmentioning
confidence: 99%
“…28 Cell sorting DN1-4 populations were sorted, using anti-CD25 FITC , -CD4/8 PE , and -CD44 Cychrome . Staining with anti-CD4 PE and -CD8 Cychrome allowed sorting of DP and SPs, on MoFlo (Cytomation, Fort Collins, CO).…”
Section: Pcr Analysismentioning
confidence: 99%